2020
DOI: 10.1088/1361-6463/ab651a
|View full text |Cite
|
Sign up to set email alerts
|

An optical-transparent metamaterial for high-efficiency microwave absorption and low infrared emission

Abstract: An optically transparent metamaterial structure with simultaneously broadband microwave absorptivity and low infrared (IR) emissivity is proposed. Two specifically designed optically transparent metasurfaces were combined to realize radar and IR bi-stealth. One was designed to control the microwave absorption though properly modifying the impedance and resonance peaks of the meta-atom. The other was designed to control the IR radiation. Within a wide incident angle of ±60°, the proposed structure displays high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…In contrast, over the last few years there has been a focus on the development and fabrication of transparent absorptive and non‐reflective metasurfaces based on thin transparent conductive films. [ 7,19–29 ] These metasurfaces utilize ITO and DMD coatings which due to their low electrical conductivity are highly advantageous for RF absorbing and stealth applications, however, their higher loss precludes the design of RF transparent devices in the higher frequency ranges. In this regard, we note that a few recent studies on the design of reflect array antennas employ ITO transparent conductive coatings such that losses are minimized through subwavelength design and use of different unit cell geometries.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, over the last few years there has been a focus on the development and fabrication of transparent absorptive and non‐reflective metasurfaces based on thin transparent conductive films. [ 7,19–29 ] These metasurfaces utilize ITO and DMD coatings which due to their low electrical conductivity are highly advantageous for RF absorbing and stealth applications, however, their higher loss precludes the design of RF transparent devices in the higher frequency ranges. In this regard, we note that a few recent studies on the design of reflect array antennas employ ITO transparent conductive coatings such that losses are minimized through subwavelength design and use of different unit cell geometries.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, low emissive coatings have been extensively studied and include conductive oxides such as indium thin oxide (ITO), aluminum zinc oxide (AZO), vanadium oxide (VO 2 ), and dielectric-metal-dielectric (DMD) layer stacks. [1][2][3][4][5][6][7][8] While considerable development of various low-emissive coatings has been realized, the use of highly conductive materials for near-infrared (NIR) control results in the blockage of RF signals which makes the implementation of these devices in the smart city environment dubious. 9 To mitigate this drawback, recent studies have suggested subwavelength patterning of low-emissive films to preclude barrier properties of uniform silver films in the low RF frequency range by virtue of disconnected repeating pattern of Ag islands.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, over the last few years there has been a focus on the development and fabrication of transparent absorptive and non-reflective metasurfaces based on thin transparent conductive films. 7,[19][20][21][22][23][24][25][26][27] These metasurfaces utilize ITO and DMD coatings which due to their low electrical conductivity are highly advantageous for RF absorbing and stealth applications, however, their higher loss precludes the design of RF transparent devices in the higher frequency ranges. In this regard, we note that a few recent studies on the design of reflect array antennas employ ITO transparent conductive coatings such that losses are minimized through subwavelength design and use of different unit cell geometries.…”
Section: Introductionmentioning
confidence: 99%
“…These include lowemissivity optical coatings [1-3, 16, 19, 20], transparent conductive oxides (TCOs) in photovoltaic devices [2][3][4], transparent circuit components [4], antennas [5], metamaterials [7-10, 17, 20, 21], and various flexible devices and sensors [11,12,18]. Moreover, there has been a focus on the design and fabrication of visibly transparent low-emissive radio frequency (RF) absorbers for IR, acoustic and RF bistealth applications [18][19][20][21][22], where researchers exploit the low conductivity of thin films (e.g., ITO) for high RF absorption. Despite their successful integration in a multitude of device constructs, the limited electrical conductivity offered by these material systems along with their scarcity (e.g., ITO) prevents the realization of transparent EM devices that can also operate in the high radio frequency (RF) range (GHz-THz).…”
Section: Introductionmentioning
confidence: 99%